The Effect of Thrombolytic, Anticoagulant, and Vasodilator Agents on the Survival of Random Pattern Skin Flap - Aral, Mübin; Tuncer, Serhan; Şencan, Ayşe; Elmas, Çiğdem; Ayhan, Sühan (Journal of Reconstructive Microsurgery, 2015)
Background The aim of this study was to investigate the effect of subcutaneously applied thrombolytic, anticoagulant, and vasodilator agents on the survival of random-pattern skin flap.Methods A caudally based dorsal flap model was used in 24 rats in four groups. In group 1 (n = 6), flap was elevated and sutured. In group 2 (n = 6), enoxaparin sodium was injected subcutaneously immediately after surgery, on days 1 and 2. In group 3 (n = 6), a transdermal nitroglycerin was applied directly following surgery, on days 1 and 2. In group 4 (n = 6), alteplase was injected subcutaneously immediately after surgery, on days 1 and 2. Blood flow was measured with laser Doppler flowmetry at the proximal and distal halves of flap before, immediately after surgery, and on days 3 and 7. Histologic samples were taken from the same locations on day 3 and day 7 postoperatively. Vessel and lymphocyte count was obtained. Photographs were taken to determine flap necrosis areas at day 7 postoperatively.Results Area of skin necrosis was found to be less in all medication groups. But only enoxaparin sodium group showed significant decrease in skin necrosis (p < 0.05). Laser Doppler flowmetry showed a gradual decrease in all groups over time, with no statistically significant result. The histologic findings revealed the induction of angiogenesis in all experimental groups.Conclusion Subcutaneously applied thrombolytic, anticoagulant, and vasodilator agents increase random-pattern skin flap survival with only enoxaparin sodium showing significant decrease in flap necrosis.
Keywords: anticoagulant; thrombolytic; skin flap; vasodilator